Unified Airborne Active and Passive Microwave Measurements over Arctic Sea Ice and Ocean during the HALO-(AC)³ Campaign in Spring 2022 (v2.7) - Dorff, Henning; Aubry, Clemantyne; Ewald, Florian; Hirsch, Lutz; Jansen, Friedhelm; Konow, Heike; Mech, Mario; Ori, Davide; Ringel, Maximilian; Walbröl, Andreas; Crewell, Susanne; Ehrlich, André; et al. (PANGAEA, 2024)
The Halo Microwave Package (HAMP), deployed onboard the High Altitude and LOng range research aircraft (HALO), performed measurements over the Arctic ocean and sea-ice during the HALO-(AC)³ campaign in March and April 2022. After the transfer flight (RF01) from Oberpfaffenhofen (Germany), 17 research flight (RF) days started from Kiruna, Sweden and heading northwards to the Fram Strait and central Arctic. Here, HAMP measurements were taken in different weather conditions comprising high impact synoptic events such as warm air intrusions, atmospheric rivers, cold air outbreaks or polar lows. We provide a dataset of active and passive microwave HAMP measurements, i.e. from the cloud and precipitation radar and the radiometers respectively. The radar operates at a frequency of 35 GHz while the microwave radiometer measurements comprise 25 channels in the frequency range between 22 and 190 GHz. Our dataset delivers time-series of brightness temperatures from the radiometers, and the radar reflectivity factor and linear depolarization ratio from the radar in a unified format. The unified and processed dataset provides the post-calibrated and quality-controlled measurements from both devices in a collocated temporal 1 Hz resolution applicable for joint analysis. An adherent surface mask distinguishes between three predominant overpassed surface types (land, sea, and sea-ice). The radar measurements are further unified in a vertical grid having 30 m resolution. Our unified dataset allows for wide-spread analysis of evolving arctic cloud and moisture properties over the remote Arctic ocean.